2012
DOI: 10.3389/fnint.2012.00055
|View full text |Cite
|
Sign up to set email alerts
|

Octopaminergic modulation of contrast sensitivity

Abstract: Sensory systems adapt to prolonged stimulation by decreasing their response to continuous stimuli. Whereas visual motion adaptation has traditionally been studied in immobilized animals, recent work indicates that the animal's behavioral state influences the response properties of higher-order motion vision-sensitive neurons. During insect flight octopamine is released, and pharmacological octopaminergic activation can induce a fictive locomotor state. In the insect optic ganglia, lobula plate tangential cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 61 publications
4
30
1
Order By: Relevance
“…2B), resulting in a vastly more complex network of modulation than accounted for by either the H1 or H2 models. In addition to its role in the LPTC network, octopamine has been implicated in modulation of contrast sensitivity and motion adaptation in visual processing presynaptic to the LPTC network, presumably within the elementary motion detection circuits (de Haan et al, 2012). Because contrast has been shown to influence baseline flight speed (Straw et al, 2011), octopamine could have an indirect influence on a flies' preferred visual set point, which could also explain the slight increase in baseline flight speed that we observed.…”
Section: Research Articlementioning
confidence: 73%
“…2B), resulting in a vastly more complex network of modulation than accounted for by either the H1 or H2 models. In addition to its role in the LPTC network, octopamine has been implicated in modulation of contrast sensitivity and motion adaptation in visual processing presynaptic to the LPTC network, presumably within the elementary motion detection circuits (de Haan et al, 2012). Because contrast has been shown to influence baseline flight speed (Straw et al, 2011), octopamine could have an indirect influence on a flies' preferred visual set point, which could also explain the slight increase in baseline flight speed that we observed.…”
Section: Research Articlementioning
confidence: 73%
“…Several recent studies have concordantly shown that locomotor activity as well as systemic administration of octopamine or its agonist CDM elevates the resting activity of fly LPTCs and enhances their stimulus-induced responses (Longden and Krapp, 2009, 2010; Chiappe et al, 2010; Maimon et al, 2010; Jung et al, 2011; Haan et al, 2012; Rien et al, 2012; Suver et al, 2012). In some of these studies, the response boost was particularly strong at high temporal frequencies of grating motion (Chiappe et al, 2010; Longden and Krapp, 2010; Jung et al, 2011).…”
Section: Resultsmentioning
confidence: 94%
“…Mutant flies lacking the enzyme for the synthesis of octopamine from its precursor tyramine are impaired in flight initiation and maintenance (Brembs et al, 2007). In flies as well as in locusts, administration of octopamine or its agonist chlordimeform (CDM) was shown to affect visual processing (Bacon et al, 1995; Longden and Krapp, 2009, 2010; Jung et al, 2011; Haan et al, 2012; Rien et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has shown that many of these behaviours are either more complex than initially imagined [1619] or liable to exploitation [20]. Moreover, several studies have shown that the state of the animal modulates how sensory structures process identical stimuli [2126] and many of these modulations are caused by aminergic actions [1,2,21,2729]. Owing to observations like these, the general concept of behaviours as responses to external stimuli (sensorimotor hypothesis) has come under ever more critical scrutiny in the last decade.…”
Section: Introductionmentioning
confidence: 99%